A diverted submarine channel of Early Cretaceous age revealed by high-resolution seismic data, SW Barents Sea. (December 2018) - Corseri, Romain; Faleide, Thea Sveva; Faleide, Jan Inge; Midtkandal, Ivar; Serck, Christopher Sæbø; Trulsvik, Mikal; Planke, Sverre
Abstract: Mud-rich prograding sediment lobes make for most of the Barremian – Albian stratigraphic record in the SW Barents Sea. Submarine canyons and channels potentially represent key components of sediment transport from shelf to basin floor but geological evidences are lacking. We present high-resolution seismic data and scrutinize an elongated, ∼150-km long bright seismic amplitude and resistive anomaly located alongslope of a NW-sourced Barremian delta in the SW Barents Sea. Seismic interpretation is performed on a comprehensive database comprising 3D/2D high-resolution P-Cable and conventional seismic data, tied to three exploration wells to provide age-control on key horizons. Our results highlight that the elongated geophysical anomaly originates from a soft layer deposited over a harder, erosional surface. The erosive morphology displays three narrow, V-shaped incisions to the NE of the Hoop area which develop into a single, ∼6 km-wide, U-shaped channel towards the transition to the Fingerdjupet Subbasin. The geological feature is named Ceres and interpreted as a submarine channel carved in Aptian, a period of marked sea level rise and sediment starvation in the Hoop area. An evolutionary model of a diverted submarine channel is proposed where a flooded delta lobe acted as a topographic barrier, funneling bottom currents and thereby carving an alongslope, possibly contouritic channel. This is the first documented case of a submarine channel pathway – delta lobe interaction on the Norwegian continental shelf. To account for the geophysical expression of Ceres, two competing explanations are discussed: (1) hydrocarbon-bearing sands, and (2) organic-rich source rock. Both scenarios have important implications for petroleum prospectivity: a faulted stratigraphic trap holding large volumes of hydrocarbons or alternatively the channel-controlled distribution of mature Aptian source rock in the SW Barents Sea. Graphical abstract: Highlights: Ceres is an elongated bright seismic event and a prominent resistor. High-resolution seismic data reveal an erosive channel in Lower Cretaceous. A diverted submarine channel is carved in Aptian in the SW Barents Sea. A flooded Barremian delta lobe acted as topographic barrier for bottom currents. Hydrocarbon-saturated sands or source rock could explain the geophysical anomalies.